Scheme analysis of transmission network for 5G mobile communication system - Lili WANG; Jun YAO (Dianxin kexue)
The service requirements of the three typical scenarios in the 5G era put forward higher requirements on the capacity, delay and networking flexibility of the bearer network. At the same time, the changes of the wireless network and the core network architecture propose the requirements of network slicing and enhanced routing and forwarding functions. Firstly, the 5G bearer requirements were analyzed, and the 3G typical service scenarios of 5G and the architecture changes of the wireless and core networks were considered. Then, based on the actual application of the 100GE PTN, the benchmarking of the demand and the status quo of the network was completed mainly around dimensions such as capacity, latency, etc. Finally, the evolution plan of network backhaul and computer room supporting was proposed.